(untitled) (Research, Society and Development, 2022)
Pyometra is a condition of the female reproductive system, mediated by hormones and secondary to bacterial infections, which is present in all species of domestic animals. It can be classified as open or closed pyometra, which is the most severe form. This work aims to carry out a literature review about pyometra in bitches regarding the concept, classifications, occurrence, pathophysiology, etiological agents, clinical signs, differential diagnoses, diagnosis and treatment. The study is of a qualitative nature. In this one, a bibliographic review was carried out on the theme of the cystic endometrial hyperplasia-canine pyometra complex. In this way, topics such as classification, pathophysiology, clinical signs, complementary exams, treatment and prognosis were addressed, using articles from 2010 to 2021. Pyometra is a serious disease that, when not identified and treated correctly, can lead the animal to death. Due to the high occurrence of the pathology in the veterinary routine, a good understanding of the disease is very important.